2019
DOI: 10.1108/ijem-11-2017-0338
|View full text |Cite
|
Sign up to set email alerts
|

The effect of highly emotionally intelligent teachers on their students’ satisfaction

Abstract: Purpose The purpose of this paper is to answer the basic research question “Do highly emotional intelligent teachers increase student’s satisfaction in the universities?” Design/methodology/approach The paper is a quantitative study using self-reporting questionnaires applied on 283 students and 10 faculty members. Findings The paper shows the importance of having high emotional intelligent teachers in the universities to increase students’ emotional intelligence (EI) and, therefore, their satisfaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
19
0
3
Order By: Relevance
“…This ratio may be because more emotionally intelligent teachers can adopt a reflexive attitude toward conflict they are confronted with, due to a greater capacity to identify their emotions and adjust them appropriately, as opposed to teachers who have less EI. As some authors indicate, individuals with high EI are more confident, creative, flexible, and better able to cope with their own emotions, with greater problem solving and conflict negotiation skills (Hein, 1996;Maamari and Majdalani, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ratio may be because more emotionally intelligent teachers can adopt a reflexive attitude toward conflict they are confronted with, due to a greater capacity to identify their emotions and adjust them appropriately, as opposed to teachers who have less EI. As some authors indicate, individuals with high EI are more confident, creative, flexible, and better able to cope with their own emotions, with greater problem solving and conflict negotiation skills (Hein, 1996;Maamari and Majdalani, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researches also showed the effectiveness of positive action in the development of teachers' emotional skills, increasingly recognizing teachers being emotionally intelligent as the basis for a good relationship with students, for providing a steady and wholesome classroom environment (Maamari and Majdalani, 2019). Other researches confirmed that school teachers' EI is a stress and burnout protection factor (Brackett et al, 2010;Schoeps et al, 2019), associated to higher professional performance, lower feelings of tiredness (Extremera et al, 2016), helpful for the teaching-learning process (Chan, 2006), related to promotion of an appropriate emotional climate (Jennings and Greenberg, 2009), and also to an effective classroom management (Valente, 2019).…”
Section: Emotional Intelligence In the Classroommentioning
confidence: 99%
“…Many studies have shown that EI is vital for school teachers' work performance and personal interactions [17]. It has been shown to correlate, for example, with all the following factors: well-being, job and life satisfaction [13]; teacher-student relationships, stress-tolerance and teaching satisfaction [18]; burnout prevention [19]; student satisfaction [20]; emotional labor strategies, teaching satisfaction, and the teaching and learning process [21]; and with classroom conflict management [7]. So, Mérida-López et al [6] have concluded that school teachers with higher EI scores showed greater coping resilience and higher work engagement levels.…”
Section: Teachers' Emotional Intelligencementioning
confidence: 99%
“…Teaching requires great emotional labor and teachers EI is recognized as the basis of their http://dx.doi.org/10.21615/cesp.13.2.2 attitudes toward their students and to provide a steady and wholesome classroom environment (Hen & Sharabi-Nov, 2014). Also, teachers recognized the importance of EI in classrooms and how it becomes a crucial constituent of the teaching-learning process resulting in holistic learning and development of students (Allen et al, 2014;Becker et al, 2014;Maamari & Majdalani, 2019;Pugazhenthi & Srinivasan, 2018). Besides, different studies showed that EI is positively correlated with teacher's efficacy (Hassan et al, 2015;Koçoğlu, 2011;Wenn et al, 2018), and with classroom management efficacy (Valente et al, 2019;Wahyuddin, 2016).…”
Section: Teacher's Emotional Intelligence Capacitiesmentioning
confidence: 99%
“…For teachers, it is not enough to have only academic knowledge, it is also essential having emotional knowledge. Studies on teacher's emotional intelligence (EI) have already provided evidence that EI is the foundation for positives relationships, and for a good functioning in a school environment (Hargraves, 2017;Maamari & Majdalani, 2019), namely concerning the benefits regarding professional performance, (Cejudo & López-Delgado, 2017), teaching and learning process (Allen et al, 2014), students' school achievement (Becker et al, 2014), job satisfaction (Cejudo & López-Delgado, 2017), reducing stress and burnout (Subalakshmi et al, 2019), and the significance for interpersonal relationships in an educational context (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%